Motivasi Masyarakat Aceh Dalam Menggunakan Aplikasi Tiktok - Ade Irma; Rizki Amelia (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
The TikTok application is loved by young Indonesians, especially in Aceh. Various content is presented in the TikTok application, thus making users interested and immersed in the content presented by content creators. This study aims to determine the motivation of the Acehnese people in using the TikTok application. To get answers to these two objectives, researchers used qualitative methods. The data collection techniques were carried out by observing and interviewing informants aged 20-40 years. The results showed that the people of Aceh were motivated to use the TikTok application for reasons due to the community's need to interact with the wider community as a form of self-actualisation in cyberspace, the TikTok application as a place to store one's memorable moments in the form of photos and videos, and other motivations are to express themselves through TikTok media.